Evaluation of a prototype dynamic laryngoplasty system in vitro with an equine vacuum airflow system. Issue 2 (20th December 2018) - Ahern, Benjamin J.; Lukas, Emily; Lam, Kimberly; Wilke, Emma; Bertin, Francois‐Rene; Van Eps, Andrew; Franklin, Samantha
Abstract: Objective: To evaluate a prototype dynamic laryngoplasty system (DLPS) in a static airflow model. Study design: Experimental. Sample population: Ten equine larynges. Methods: The right arytenoid was fixed in abduction in all specimens. A left‐sided laryngoplasty was performed with No. 2 Fiberwire and a FASTakII anchor. Each larynx was tested in a static airflow model. The system was adjusted to a flow rate of 55 L/s and prelaryngeal pressure of 12 mm Hg prior to testing in maximal arytenoid abduction. In phase 1, the left suture was loosened, shortened, and tested in 3‐mm steps from 0 to 30 mm. In phase 2, the suture was tied with the DLPS in position at a target left‐to‐right quotient angle (LRQ) of 0.5. The DLPS was activated to target psi of 0, 25, and 50 for testing. Translaryngeal impedance (TLI), LRQ, cross‐sectional areas (CSA), and resultant change in LRQ and CSA between, before, and during airflow testing were calculated. Results: In phase 1, TLI was reduced by suture shortening up to 6 mm ( P  = .001) but not by additional shortening ( P  > .05). In phase 2, activation of the DLPS reduced the TLI from 0 psi (0.43 ± 0.08 mm Hg/L/s) to 25 psi (0.16 ± 0.04 mm Hg/L/s, P  < .001), but no further reduction was detected at maximal psi ( P  = .10). Conclusion: Activation of the DLPS effectively reduced TLI. Clinical significance: These results justify further investigation of the DLPS to assess its clinical applicability.